Bax mRNA Expression as A Potential Biomarker of Placental Apoptosis in Early-onset Preeclampsia - Muhammad Javedh Iqbal; Diah Rumekti Hadiati; Didik Setyo Heriyanto (The Indonesian Biomedical Journal, 2023)
BACKGROUND: Early-onset preeclampsia is characterized by higher oxidative stress and apoptosis level than late-onset one. Studies comparing the expression of the Bcl-2 family protein in early and late-onset preeclampsia are still lacking and show inconclusive evidence. This study aimed to compare the expression of Bax and Bcl-2 messenger RNA (mRNA) as a biomarker of placental apoptosis between early-onset and late-onset preeclampsia.METHODS: A cross-sectional study was conducted using formalin-fixed, paraffin-embedded preeclamptic placental samples and dividing them into early-onset and late-onset preeclampsia groups. Bax and Bcl-2 mRNA expressions were assessed using the quantitative real-time polymerase chain reaction method. Apoptosis was assessed through DNA fragmentation examination by the ligation-mediated real-time polymerase chain reaction method.RESULTS: Thirty early-onset and 30 late-onset preeclamptic placental samples were included. The mean fold change Bax mRNA in early-onset was higher than in late-onset preeclampsia (6.02±3.59 vs. 2.82±1.97; p=0.00). The mean fold change Bcl-2 mRNA early-onset was not different from late-onset preeclampsia (31.20±17.94 vs. 31.01±27.60; p=0.98). The mean DNA fragmentation cycle threshold in early-onset preeclampsia was lower than in late-onset preeclampsia (28.07±0.64 vs. 30.63±0.96; p=0.00). A weak negative correlation exists between fold change Bax mRNA and DNA fragmentation cycle threshold (r=-0.30; p=0.02).CONCLUSION: Bax mRNA showed significant correlation in DNA fragmentation compared to Bcl-2 mRNA; hence, might show more role in apoptotic pathway. Early-onset preeclampsia has higher Bax mRNA relative expression and apoptosis than late-onset preeclampsia. Therefore, Bax mRNA can be potential biomarker in early-onset preeclampsia.KEYWORDS: mRNA, Bax, Bcl-2, apoptosis, DNA fragmentation, early-onset, preeclampsia